Pharmacological Inhibition of Indoleamine 2,3-Dioxygenase-2 and Kynurenine 3-Monooxygenase, Enzymes of the Kynurenine Pathway, Significantly Diminishes Neuropathic Pain in a Rat Model - Rojewska, Ewelina; Ciapała, Katarzyna; Piotrowska, Anna; Makuch, Wioletta; Mika, Joanna (Frontiers in Pharmacology, 2018)
Neuropathic pain caused by a primary injury or dysfunction in the peripheral or central nervous systems is a tremendous therapeutic challenge. Here, we collected the first evidence revealed in one study on the potential contributions to neuropathic pain development by enzymes in the kynurenine pathway [tryptophan 2,3-dioxygenase (Tdo), indoleamine 2,3-dioxygenase (Ido1/2), kynurenine 3-monooxygenase (Kmo); kynureninase (Kynu), 3-hydroxyanthranilate-3,4-dioxygenase (Haoo)] at the spinal cord and DRG levels. At the spinal cord mRNA level of Ido2, Kmo and Haoo were elevated as measured on day 7 after CCI, parallel to the C1q-positive cell activation. According to our data obtained from primary microglial cell cultures, all enzymes of the kynurenine pathway except Tdo are derived from these cells; however, the activation of microglia induced stronger changes in Ido2 and Kmo. Our pharmacological studies give evidence that repeated intraperitoneal administration of minocycline, a microglia/macrophage inhibitor, not only attenuated tactile and thermal hypersensitivity but also diminished the levels of Ido2 and Kmo mRNA. Our further pharmacological studies confirm that Ido2 and Kmo enzymes take part in the development of neuropathic pain, since we observed that repeated administration of Ido2 (1-Methyl-D-tryptophan) and Kmo (UPF 648) inhibitors diminished hypersensitivity development as measured on days 2 and 7. The results of our studies show that the kynurenine pathway is an important mediator of neuropathic pain pathology and indicate that Ido2 and Kmo represent novel pharmacological targets for treating neuropathy.